PEMANFAATAN LIMBAH PATI ONGGOK DAN SEKAM PADI SEBAGAI BAHAN DASAR PANEL DINDING RINGAN YANG TANGGAP GEMPA - Dini Pratiwi; Anindya Septiasti Tejowati; Muhammad Faisol Rusdiyanto; Kurniawan Jaya Sasmita; Titik Efianti (Universitas Islam Indonesia, 2016)
One cause is shortage of housing in Indonesia is caused by the high, of construction to build a shelter and to minimize the high cost of construction is one of them is to use a cheaper alternative wall panel quality. In addition, Indonesia as a country that is vulnerable to earthquake shocks require earthquake response of buildings in order to anticipate the existence of damage and casual ties, In the article the results of this research, to create a lightweight wall panel including earthquake, the main material used is waste cassava starch and rice husk as filler and resin as matrix. The purpose of this article is to provide alternative building materials solution that responds to earthquake shocks so it can be recommended as a wall panel including earthquake. The method used in the process of research is puce research method in the laboratory while the analysis method is to use comparisons with the theories of reference. In the process of material research, done by finding the exact composition of resin, fiber starch, cassava and cassava pellets to obtain good mechanical characteristics. Results of laboratory tests showed that the composite panels on specific compositions have high mechanical characteristics.Keywords: resins, waste cassava starch, rice husks, mechanical characteristics, earthquakeresponce.